Cutaneous graft-versus-host disease after hematopoietic stem cell transplant - a review - Villarreal Villarreal, César Daniel; Alanis, Julio Cesar Salas; Pérez, Jose Carlos Jaime; Candiani, Jorge Ocampo (2016)
Graft-versus-host disease (GVHD) is a major complication of allogeneic hematopoietic stem cell transplants (allo-HSCT) associated with significant morbidity and mortality. The earliest and most common manifestation is cutaneous graft-versus-host disease. This review focuses on the pathophysiology, clinical features, prevention and treatment of cutaneous graft-versus-host disease. We discuss various insights into the disease’s mechanisms and the different treatments for acute and chronic skin graft-versus-host disease.